A STRATEGIC APPROACH TO ORGANISATIONAL ENTREPRENEURSHIP: EMPLOYEES’ AWARENESS OF ENTREPRENEURIAL STRATEGY - Erić Nielsen, Jelena; Marinković, Veljko; Nikolić, Jelena (Economic Annals, 2019)
The purpose of the paper is to explore employees’ awareness of the en-trepreneurial strategy in an organisation. We argue that employee awareness of the clarity and flexibility of entrepreneurial strategy differs depending on gender, age, seniority, education, and working experi-ence. We provide a theoretical overview explaining the interaction between per-formance-oriented strategic management and entrepreneurship, based on organ-isational innovation. Our study delin-eates the specifics of a strategic approach to organisational-level entrepreneurship, explaining in depth the integration of en-trepreneurship and strategy. The data was collected from a total of 39 managers and 50 employees holding non-managerial po-sitions in 19 Serbian companies. The results of the analysis show a statistically signifi-cant difference in employees’ awareness of the clarity and flexibility of entrepreneurial strategy, depending on gender, level of edu-cation, and seniority. The research presents empirically and theoretically substantiated evidence regarding the necessity to make entrepreneurial strategy an integral part of corporate strategy and to make employees aware of the relevance of strategy in achiev-ing long-term competitive advantage. Based on these considerations the results are critically evaluated their implications and limitations are discussed, and avenues for further research are recommended.